Downregulated Dopamine Receptor 2 and Upregulated Corticotrophin Releasing Hormone in the Paraventricular Nucleus Are Correlated With Decreased Glucose Tolerance in Rats With Bilateral Substantia Nigra Lesions - Zhou, Li; Ran, Xue-Rui; Hong, Feng; Li, Guang-Wen; Zhu, Jin-Xia (Frontiers in Neuroscience, 2019)
Patients with Parkinson’s disease (PD) have a high prevalence of glucose metabolism abnormalities. However, the mechanism underlying these symptoms remains unclear. The hypothalamic-pituitary-adrenal (HPA) axis is the major neuroendocrine axis that regulates homeostasis in mammals, including glucose metabolism. Corticotrophin releasing hormone (CRH), which is synthesized in the paraventricular nucleus (PVN) of the hypothalamus, plays an important role in the regulation of blood glucose levels via the HPA axis. Our previous studies have reported that PVN neurons express numerous dopamine receptors (DRs) and accept direct projections from the substantia nigra (SN). We hypothesize that damage to dopaminergic neurons in the SN might influence the blood glucose level through the HPA system. Rats with bilateral SN lesions induced by 6-hydroxydopamine (6-OHDA) (referred to as 6-OHDA rats) were used to investigate alterations in the levels of blood glucose, CRH, and factors related to the HPA axis and to explore possible mechanisms. Blood glucose levels were detected at different time points after the glucose solution was intraperitoneally administered. CRH and DRs in the PVN were evaluated by immunofluorescence and western blot analysis. Adrenocorticotropic hormone (ACTH) in the pituitary and plasma corticosterone (CORT) was evaluated by radioimmunoassay (RIA). The results showed that 6-OHDA rats exhibited significantly decreased tyrosine hydroxylase (TH) in the SN and decreased glucose tolerance at 6 weeks, but not at 4 weeks. In the PVN, dopamine receptor 2 (D2) was expressed on CRH-positive neurons, and D2-positive neurons were surrounded by TH-positive fibers. Additionally, the expression of CRH was upregulated, whereas the expression of D2 and TH were downregulated in 6-OHDA rats compared with control rats. In D2 knock-out mice, the significantly enhanced expression of CRH and reduced expression of D2 were detected in the PVN. Furthermore, RIA revealed increased ACTH in the pituitary and elevated CORT in the blood. In summary, the present study suggests that the dopaminergic neurons in the SN are involved in the regulation of body glucose metabolism through CRH neurons that express D2 in the hypothalamic PVN. SN lesions decrease glucose tolerance mainly by downregulating D2 and upregulating CRH in the PVN through the HPA neuroendocrine system.